Perilaku Hidup Bersih dan Sehat Santri Pondok Pesantren As'ad dan Pondok Pesantren Al Hidayah - NOFRAN PSIKOLOGI; Tina Yuli Fatmawati; Nofrans Eka Saputra (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2017)
INTRODUCTION Pondok Pesantren in Indonesia, many have a very classic problem i.e about the health of santri and problems with diseases. Health problems and diseases in pesantren is very rarely gets attention by both the citizens of the pesantren and society, also governments. The purpose of this study is to know the representation of the clean and healthy behaviour of santri at Pondok Pesantren As'ad and Al-Hidayah in 2015.METHOD This research is a descriptive study that aims to know the representation of santri clean and healthy behavior who were living in the Pondok Pesantren As'ad and Al-Hidayah in 2015. The population of this study were all santri at Pondok Pesantren As'ad and Alhidayah numbering 842 santri. Samples were taken using Proportional Random Sampling technique with total 89 santri. The research instrument used questionnaire. Collected data is by distributing questionnaires. Data analyzed using univariate analysis.RESULTS Research shows that santri in Pondok Pesantren As'ad who have a good clean and healthy life behavior either by 14 (51.9%) and respondents who have less clean and healthy life behavior are by 13 (48.1%). While in Pondok Pesantren Al-Hidayah shows that respondents who have were good clean and healthy life behavior either 39 (62.9%), respondents who have less clean and healthy life behavior were by 20 (32.3%), and respondents have life behavior excellent clean and healthy 3 (5%). The advice for health personnel and the boarding school are to increase knowledge by providing counseling to the santri about the behavior of clean and healthy. CONCLUSIONS AND RECOMENDATIONS The advice for health personnel and the boarding school are to increase knowledge by providing counseling to the santri about the behavior of clean and healthy. Keywords : Healthy Lifestyle and Clean Practise, Santri, Pondok Pesantren